Classification and Problems in Process of Translation of Lexical Transformations (Texas Journal of Agriculture and Biological Sciences, 2023)
The article discusses the essence of lexical transformations in the process of translation, its classification and the main issues faced during the translation process. The theories presented in the given article are supported with proper examples in both English and Russian languages.